2012
DOI: 10.1038/onc.2012.319
|View full text |Cite
|
Sign up to set email alerts
|

Tumour cell responses to new fibroblast growth factor receptor tyrosine kinase inhibitors and identification of a gatekeeper mutation in FGFR3 as a mechanism of acquired resistance

Abstract: Fibroblast growth factor receptors (FGFRs) can act as driving oncoproteins in certain cancers, making them attractive drug targets. Here we have characterized tumour cell responses to two new inhibitors of FGFR1-3, AZ12908010 and the clinical candidate AZD4547, making comparisons with the well-characterized FGFR inhibitor PD173074. In a panel of 16 human tumour cell lines, the anti-proliferative activity of AZ12908010 or AZD4547 was strongly linked to the presence of deregulated FGFR signalling, indicating tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
113
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(122 citation statements)
references
References 58 publications
8
113
0
1
Order By: Relevance
“…3A). Gatekeeper mutations which impair drug binding in the ATP-binding pocket of FGFR were previously identified as a mechanism of resistance in cell linebased assays (29,30). Consistent with this, we observed the emergence of a FGFR2 V565F gatekeeper mutation in GAGA6-R ĂŸ -resistant cells (Fig.…”
Section: Azd4547 Resistance In Cell Culture-derived (Gaga6-r ĂŸ ) and supporting
confidence: 75%
See 3 more Smart Citations
“…3A). Gatekeeper mutations which impair drug binding in the ATP-binding pocket of FGFR were previously identified as a mechanism of resistance in cell linebased assays (29,30). Consistent with this, we observed the emergence of a FGFR2 V565F gatekeeper mutation in GAGA6-R ĂŸ -resistant cells (Fig.…”
Section: Azd4547 Resistance In Cell Culture-derived (Gaga6-r ĂŸ ) and supporting
confidence: 75%
“…In contrast to cell line-based studies (29), GAGA6 PDX tumors that were under continuous AZD4547 treatment in vivo did not develop gatekeeper mutations in the ATP-binding pocket of FGFR2. The lack of gatekeeper mutations in AZD4547-resistant cells was also observed in another FGFR2-amplified PDX, GAGA3, when subjected to AZD4547 selection in vivo (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…However, several preclinical models have pointed to possible mechanisms of resistance against FGFR therapies. In MM cell lines, a gatekeeper mutation in FGFR3 (FGFR3 V555M) is involved in resistance to AZD4547 and PD173074 (both Pan-FGFR Inhibitors) (Chell et al, 2013). In endometrial cell lines, several FGFR2 point mutations (especially V564I) have been reported to confer different degrees of resistance to multi-target inhibitors (Dovitinib, Ponatinib and PD173074) (Byron et al, 2013).…”
Section: Resistance To Therapiesmentioning
confidence: 99%